VISUALISASI INTRUSIVE THOUGHTS DALAM KARYA FILM EKSPERIMENTA - Shafy Putra, Muhammad; Wiwid Sintowoko, Dyah Ayu; Permana Zen, Adrian (eProceedings of Art & Design, 2024)
The making of this experimental 昀椀lm en琀椀tled Intrusive Thoughts is a 昀椀lm work that discusses intrusive thoughts, namely nega琀椀ve thoughts in the form of imagina琀椀on or thoughts that are brutal, or appear in the form of violence, sexual, and create cogni琀椀ve disorders that if followed will endanger others. This work is inspired by the phenomenon of intrusive thoughts in the journal "Journal of Obsessive-Compulsive and Related Disorders". This experimental 昀椀lm explores how intrusive thoughts can a昀昀ect cogni琀椀ve ac琀椀vity through symbolic and meaningful scenes. The 昀椀lm aims to raise awareness about intrusive thoughts, as a medium of expression and explora琀椀on to channel personalanxie琀椀es, and help people who experience Intrusive Thoughts to feel more understood and less alone. Experimental 昀椀lm is the medium chosen to raise and discuss this phenomenon. In the discussion of the work, the author will discuss the elements of experimental 昀椀lm,namely abstract form and associa琀椀onal form displayed through color, symbols, movement, music, and sound. Keywords: : Intrusive Thoughts, intrusive thoughts, cogni琀椀ve impairment, experimental昀椀lm